(Invited) Control of Atomic Layer Reactions in Plasma Processing. (16th August 2016) - Ventzek, Peter; Sherpa, S D; Wang, M; Rastogi, V; Ranjan, Alok
Abstract : Control of atomic layer reactions in discrete adsorption and desorption steps is what enables atomic layer etching (ALE) and escape of process trade-offs for 7 nm technologies and beyond. Silicon ALE has been demonstrated but challenges remain mating precursors, process chambers and materials in ALE for other materials. This brief paper reviews recent activity devoted to the engineering of silicon, oxide and nitride material ALE. Hybridized ALD-ALE and ALD-Etch processes are discussed which may overcome the challenges posed by the etch of oxide and nitride materials for patterning, contact and memory applications.